Design and application for the model of semantic query expansion based on domain ontology. (10th July 2012) - Liu, Ziyu; Chen, Junxia; Li, Xuehui; Qu, Ying; Li, Fachao
Ontology method has become an important method in computer science, and it has been used in many domains, such as semantic web, search engine and knowledge management. Ontology plays an important role in semantic retrieval because of its specification, its good concept hierarchy and its support for logical reasoning. Domain ontology can be used to extend the user's retrieval words and index domain knowledge. Under which we can achieve semantic retrieval for domain knowledge. The semantic extension of user's retrieval words is the more important step in semantic retrieval system. First, this paper designed the model of semantic query expansion based on domain ontology and gave five kinds of semantic expansion methods. Then the model of semantic query expansion is applied in semantic retrieval system. The designed system consists of four main components: ontologies building, retrieval words semantic extension, semantic precomputation for document and semantic retrieval. Finally, this paper makes an experiment on high-speed railway domain. The experimental results show that the developed semantic retrieval system can improve the recall and precision.